Long cold exposure induces transcriptional and biochemical remodelling of xylem secondary cell wall in Eucalyptus. (13th June 2017) - Ployet, Raphael; Soler, Marçal; Carocha, Victor; Ladouce, Nathalie; Alves, Ana; Rodrigues, José-Carlos; Harvengt, Luc; Marque, Christiane; Teulières, Chantal; Grima-Pettenati, Jacqueline; Mounet, Fabien
Abstract: Although eucalypts are the most planted hardwood trees worldwide, the majority of them are frost sensitive. The recent creation of frost-tolerant hybrids such as Eucalyptus gundal plants ( E. gunnii × E. dalrympleana hybrids), now enables the development of industrial plantations in northern countries. Our objective was to evaluate the impact of cold on the wood structure and composition of these hybrids, and on the biosynthetic and regulatory processes controlling their secondary cell-wall (SCW) formation. We used an integrated approach combining histology, biochemical characterization and transcriptomic profiling as well as gene co-expression analyses to investigate xylem tissues from Eucalyptus hybrids exposed to cold conditions. Chilling temperatures triggered the deposition of thicker and more lignified xylem cell walls as well as regulation at the transcriptional level of SCW genes. Most genes involved in lignin biosynthesis, except those specifically dedicated to syringyl unit biosynthesis, were up-regulated. The construction of a co-expression network enabled the identification of both known and potential new SCW transcription factors, induced by cold stress. These regulators at the crossroads between cold signalling and SCW formation are promising candidates for functional studies since they may contribute to the tolerance of E. gunnii × E. dalrympleana hybrids to cold.